Antibiotic prescribing for children five years or younger in Indonesian primary care settings - Wibowo, Yosi Irawati; Firdhausi, Niken; Rahmah, Nur; Setianur, Noviana; Sunderland, Bruce; Setiadi, Adji Prayitno (The Journal of Infection in Developing Countries, 2025)
Introduction: Children are at a higher risk of antibiotic overprescribing, while limited surveillance is evident in primary care settings. This study aims to examine patterns of infections and associated antibiotic use in children attending Primary Health Centers (PHCs), including an explanatory analysis of antibiotics for non-pneumonia acute respiratory infections (ARIs), pneumonia, and diarrhea. Methodology: An observational study used records of all children  5 years of age prescribed antibiotics from January 2019 to December 2020 in selected PHCs in Surabaya and Banjarmasin, Indonesia. Data on children’s characteristics, diagnoses, and antibiotics prescribed, were collected from patient records. The explanatory analysis was based on national guidelines. A descriptive analysis was used to summarize the data. Results: A total of 1053 and 1463 children’s records with antibiotics were located at Surabaya and Banjarmasin PHCs, respectively. ARIs were the most common indications for antibiotic prescribing in both settings, either non-pneumonia ARIs (60.6% versus 33.8%, respectively) or pneumonia (20.2% versus 25.2%, respectively). High conformity with guidelines were evident for antibiotics used for pneumonia (i.e., amoxicillin/cotrimoxazole/erythromycin – 89.3%) or specified upper ARIs (e.g., amoxicillin for pharyngitis – 73.9%), and for diarrhea (i.e., cotrimoxazole – 73.1%). However, some information, such as diagnoses, were not recorded or were unspecific, hence limiting assessment. Conclusions: This study provided insights into prescribing antibiotics among children in Indonesia. Lack of specific guidelines for children and inadequate documentation for antibiotic prescribing warrants improvement. Larger prospective studies should assess appropriate prescribing at the national level to optimize the use of antibiotics.